Associations between respiratory and vascular function in early childhood. Issue 11 (2nd August 2021) - Hemstock, Emily J.; Shao, Jingyi; Zhao, Bing; Hall, Graham L.; Wheeler, Amanda J.; Dharmage, Shyamali C.; Melody, Shannon M.; Dalton, Marita F.; Foong, Rachel E.; Williamson, Grant J.; Chappell, Katherine J.; Abramson, Michael J.; et al.
Abstract: Background and objective: The link between respiratory and vascular health is well documented in adult populations. Impaired lung function is consistently associated with thicker arteries and higher incidence of cardiovascular disease. However, there are limited data on this relationship in young children and the studies that exist have focussed on populations at high risk of cardiorespiratory morbidity. We determined if an association exists between respiratory and cardiovascular function in young children and, if so, whether it is confounded by known cardiorespiratory risk factors. Methods: Respiratory and vascular data from a prospective cohort study established to evaluate the health implications 3 years after coal mine fire smoke exposure in children aged 3–5 years were used. Respiratory function was measured using the forced oscillation technique and included resistance at 5 Hz ( R 5 ), reactance at 5 Hz ( X 5 ) and area under the reactance curve (AX). Vascular health was measured by carotid intima‐media thickness (ultrasound) and pulse wave velocity (arterial tonometry). Regression analyses were used to examine the relationship between the respiratory Z ‐scores and cardiovascular measures. Subsequent analyses were adjusted for potential confounding by maternal smoking during pregnancy, maternal education and exposure to fine particulate matter <2.5 μm in aerodynamic diameter (PM2.5 ). Results: Peripheral lung function ( X 5 and AX), but not respiratory system resistance ( R 5 ), was associated with vascular function. Adjustment for maternal smoking, maternal education and early life exposure to PM2.5 had minimal effect on these associations. Conclusion: These observations suggest that peripheral lung stiffness is associated with vascular stiffness and that this relationship is established early in life. Abstract : Associations between respiratory and vascular function in early childhood. We found a relationship between peripheral lung stiffness and vascular stiffness in young children. This association was independent of a number of known confounding factors suggesting that this relationship is established in early life and driven by links between these physiological systems and global tissue stiffness.